As cláusulas gerais no sistema processual brasileiro e a efetividade da decisão judicial : uma análise sobre a aplicabilidade do § 5º do art. 461 do CPC - Victor, Alexandre José Gois Lima de (2012)
The normative texts or statements work as the physical basis from which the legal interpreter builds the norm that can assume a form of principle or rule. These normative texts usually consist on a double-structured statement, containing the normative antecedent and the legal consequent. The general clauses (substantive and procedural) represent a linguistic mechanism used by the legislator to produce a sort of open normative text. Therefore, the general clauses are built with both normative antecedent and consequent containing terms and expressions known as undefined legal concepts, which cannot primarily and completely establish the factual hypothesis nor the consequences. This essay aims to place, analyze, identify, conceptualize and systematize the general clauses within Brazilian civil procedural law, with special attention to that extracted from the sole paragraph of article 461 of the Brazilian Code of Civil Procedural (CPC), commonly called executive general clause or effectuation power, from which arises the possibility of a magistrate, respecting certain beacons, elect or establish a legal consequent (considered a more efficient and appropriate measure) as a way to compel the recipient of his order to its fulfillment, in order to give it a greater effectiveness. The study also highlights the argumentative onus and the forms of reasoning used in court decisions based on the appliance of procedural general clauses. At this point, it also highlights the importance of the precedents and the technic of its analysis, called case groups, not forgetting to discuss the means of control of such decisions. From the developed study it is possible to observe that the procedural general clauses are important devices, made to provide and improve the cooling of the Brazilian procedural system, accounting that they represent windows through which the legal applicator is able to incorporate to a given case a variety of elements that can be already predicted by the legal system, or not.